(untitled) (Diametros, 2010)
Plato arguably stands as one of the precursors to what we today know as the Just War Tradition, and he has more to say about ethics and the use of force than what is often acknowledged. In this article I try to show, by analyzing selected passages and perspectives from the Republic, that Plato regards the role of military ethics as crucial in the construction of the ideal city, and he sees limitation of brutality and more generally a philosophical approach to the use of force as crucial elements of the city’s approach to warfare. Military power and, indeed, harsh preparations for it do occupy a central position in Plato’s political thought, but use of armed force is at the same time closely linked to the virtue of justice as well as the other virtues.